A catalogação de assunto: apontamentos históricos e a sistematização de regras - Martinho, Noemi Oliveira [UNESP]; Fujita, Mariângela Spotti Lopes [UNESP] (My University, 2010)
The Subject Cataloguing, in spite of its expres-sive historical trajectory in the information organization, has not been as discussed as the descriptive cataloguing, although they arise from the same process. Recovering the Cataloguing history, you can see that there is a dichotomy between the descriptive process and the subject one; the first one was emphasized for the developing of codes and interchange patterns. Nevertheless, the studies on subject cataloguing are essential to give bases to products for helping the searching of holdings. For this reason, based on the literature, it is discusses the subject cataloguing and the set of problems about a possible institution of rules/code that guides it.

La catalogación de asunto a pesar del significativo trayecto histórico en la organización de la información, no fue tan discutida como la cata-logación descriptiva, a pesar de ser oriundas del mismo proceso. Al rescatar la história de la Catalogación se percibe que ocurrió una dicotomía entre los procesos: descriptivo y de asunto, siendo que el primero recibió más énfasis para el desenvolvimiento de códigos y padrones de intercambio. No obstante, los estudios de catalogación de asunto se constituyen como un punto fundamental para sustentar productos en el auxilio de la inve-sigación de acervos. Por eso, con base en la literatura se discute la catalogación de asunto y la problemática en torno de la posible creación de reglas/códigos que la orienten
Subject cataloguing: historical notes on its standarization
La catalogación de matérias: apuntes históricos sobre su normalización
Keywords: catalogação de assunto; indexação; cabeçalhos de assuntos; Charles Ammy Cutter